Effectiveness of Nipah leaf extract (Nypa fruticans) against Streptococcus mutans biofilm as cavity cleanser - Handriutomo, Yosef Kevin; Soesilo, Diana; Aprilia, Aprilia; Parisihni, Kristanti; Rayhan, Rafialdi; Cahyani, Febriastuti (Conservative Dentistry Journal, 2025)
Background: Streptococcus mutans is the primary bacterium responsible for dental caries, found in the biofilm on the tooth surface, known as dental plaque. Before restorative treatment or cavity care for carious teeth, a cavity cleanser is necessary to remove residual bacteria that could cause secondary caries or restoration failure. Nipah leaf extract contains phenol, flavonoids, saponins, and steroids, which can destroy bacteria by denaturing proteins and damaging bacterial cell membranes. Objective: To determine the antibiofilm activity of Nipah leaf extract against Streptococcus mutans biofilm. Materials and Methods: The materials used were Nypa fruticans leaf extract prepared using the maceration method at concentrations of 1%, 5%, 10%, and 15%, with chlorhexidine gluconate as the positive control and distilled water as the negative control. Bacteria cultured in BHI media were inoculated into a 96-well flat-bottomed plastic tissue culture plate and incubated for 24 hours at 37°C. Optical Density (OD) was measured using an ELISA reader. Results: KM: 0.039; K (-): 0.887; K (+): 0.085; P1: 0.727; P2: 0.463; P3: 0.347; P4: 0.169. The Mann-Whitney test results showed significant differences between K (+) and P1 (0.000), K (+) and P2 (0.000), K (+) and P3 (0.000), K (+) and P4 (0.005), P1 and P2 (0.000), P1 and P3 (0.000), and P1 and P4 (0.000). The results were significant as p < 0.05. Conclusion: Nipah leaf extract (Nypa fruticans) can inhibit the biofilm formation of Streptococcus mutans bacteria.